Causes of long-term mortality in patients with venous thromboembolism in the real world: From the COMMAND VTE registry. Issue 219 (November 2022) - Yamashita, Yugo; Morimoto, Takeshi; Kadota, Kazushige; Takase, Toru; Hiramori, Seiichi; Kim, Kitae; Oi, Maki; Akao, Masaharu; Kobayashi, Yohei; Toyofuku, Mamoru; Inoko, Moriaki; Tada, Tomohisa; et al.
Abstract: Introduction: There is still a scarcity of data on causes of long-term mortality in patients with venous thromboembolism (VTE). Materials and methods: The COMMAND VTE Registry is a physician-initiated, retrospective, multicenter cohort study in which consecutive 3027 patients with acute symptomatic VTE among 29 centers in Japan were included between January 2010 and August 2014. We investigated detailed causes and risk factors for long-term mortality. Results: During a median observation period of 1218 days, a total of 764 patients died, and the prevalence of active cancer was higher in patients who died than in patients alive (61 % versus 10 %, P  < 0.001). The cumulative incidences of cardiac death, pulmonary embolism (PE)-related death, bleeding death, cancer death, and non-cardiovascular non-cancer death were 2.2 %, 2.9 %, 2.0 %, 16.1 %, and 6.7 % at 5 years, respectively. The incidence of cancer death increased gradually, which was the most common cause of long-term death. Among patients without active cancer, the incidence of PE-related death increased rapidly and became a plateau beyond the acute phase, whereas the incidence of non-cardiovascular non-cancer death kept increasing, which became most common in the long term. The separate multivariable analysis among patient with and without active cancer identified independent risk factors of all-cause death including a few patient characteristics among patients with active cancer and several patient characteristics among patients without active cancer. Conclusions: Cancer was the most common cause of long-term mortality, while non-cardiovascular non-cancer death became most common among patients without active cancer. Graphical abstract: Unlabelled Image